Improving the Fine Motor Ability of a Down-syndrome Student by Playing with Clay at SDLB N 64 Surabayo Lubuk Basung Kabupaten Agam - Muliar A (Universitas Negeri Padang, 2016)
This research was done due to the fact that a Sown-syndrome student had fine motor disorders at school. From the preliminary observation, it was seen that it was difficult for the student to from a circle and wring clay because of his weak hands. this research aimed at proving that playing clay could improve his fine motor ability. The hypothesis was that playing clay could improve the down-syndrome student’s fine motor ability at SDLB N 64 Lubuk Basung. The design of this research was experimental approach by using the Single Subject Research. The subject of this research was a down-shindrome student. The ability of the student was determined from his ability to from clay dough. That was the baseline condition of the student in this research. After the student was given a treatment from the researcher, the ability was again measured. Based on the result of analysis, it was found that the student’s fine motor ability was improved. At the baseline condition, the student was only able to slam, pinch, and squeeze the clay dough. The intervention of fine motor ability improved to forming one piece of dough and continued to rise into 6 pieces spheres. Thus, the hypothesis was acceptable. It was proved that playing could improve the down-syndrome student’s fine motor ability. Keywords: clay dough, Single Subject Research, down-syndrome student